Analisis Lokasi, Potongan Harga, Display Produk dan Kualitas Produk terhadap Minat Beli pada Alfamart Kayubulan - Nurhayati Husain; Deby Rita Karundeng; Moh. Afan Suyanto (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
This study aims to determine the effect of location, price discounts, product display and product quality on buying interest in .The data used in this study is primary data sourced from filling out questionnaires.The research sample amounted to 50 respondents.The analytical technique used to answer the research problem and test the hypothesis is multiple linear regression analysis.The data is processed using statistical product service solution (SPSS) applications. The results of this study are (1) there is a positive and significant effect of Location on Purchase Intention at Alfamart (Kayubulan), (2) there is a positive and significant effect of Price Discounts on Purchase Intention.(3) there is a positive and insignificant effect of Product Display on Purchase Intention.(4) there is a positive and significant effect of Product Quality on Buying Interest.